Epigallocatechin-3-Gallate (EGCG)-Inducible SMILE Inhibits STAT3-Mediated Hepcidin Gene Expression - Yu-Ji Kim; Ki-Sun Kim; Daejin Lim; Dong Ju Yang; Jae-Il Park; Ki Woo Kim; Jae-Ho Jeong; Hueng-Sik Choi; Don-Kyu Kim (MDPI AG, 2020)
Hepatic peptide hormone hepcidin, a key regulator of iron metabolism, is induced by inflammatory cytokine interleukin-6 (IL-6) in the pathogenesis of anemia of inflammation or microbial infections. Small heterodimer partner-interacting leucine zipper protein (SMILE)/CREBZF is a transcriptional corepressor of nuclear receptors that control hepatic glucose and lipid metabolism. Here, we examined the role of SMILE in regulating iron metabolism by inflammatory signals. Overexpression of SMILE significantly decreased activation of the Janus kinase 2-signal transducer and activator of transcription 3 (STAT3)-mediated hepcidin production and secretion that is triggered by the IL-6 signal in human and mouse hepatocytes. Moreover, SMILE co-localized and physically interacted with STAT3 in the nucleus in the presence of IL-6, which significantly suppressed binding of STAT3 to the hepcidin gene promoter. Interestingly, epigallocatechin-3-gallate (EGCG), a major component of green tea, induced SMILE expression through forkhead box protein O1 (FoxO1), as demonstrated in FoxO1 knockout primary hepatocytes. In addition, EGCG inhibited IL-6-induced hepcidin expression, which was reversed by SMILE knockdown. Finally, EGCG significantly suppressed lipopolysaccharide-induced hepcidin secretion and hypoferremia through induction of SMILE expression in mice. These results reveal a previously unrecognized role of EGCG-inducible SMILE in the IL-6-dependent transcriptional regulation of iron metabolism.